HUBUNGAN ANTARA DURASI PENGGUNAAN SMARTPHONESEBELUM TIDUR DENGAN KUALITAS TIDUR MAHASISWA - Neftriani " Azrul; Bayhakki " "; Misrawati " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Increased of smartphone users associated with advantage of smartphone that has many features. One of the features is unlimited internet access, so that makes a person using smartphone excessively and it raises the issue of addictive behavior which ultimately affect the health of the body, including poor sleep quality, especially for PSIK UR students who often use their smartphone for a many kinds of purposes. Smartphone addictive behavior will make someone does not know the right time to use his/her smartphone and finally will taking longer time for sleep. This research aimed to determine the relationship between the duration of using smartphones before bed to sleep quality of Nursing students at University of Riau. This research used descriptive correlation with cross sectional approach. The samples were 176 students which taken by using stratified random sampling technique that appropriate to inclusion criteria. This research used questionnaire of The Pitsburgh Sleep Quality Index (PSQI) which has been tested for validity and reliability. Univariate analysis was conducted to show frequencies distribution and bivariate analysis using Spearman Correlation test. The results showed there was a significant relationship between duration of using  smartphones before bed on the sleep quality of students with p value (0.000) <α (0.05).The results of this study suggest that students could use the smartphone wisely especially when they start to sleep at night.  Keywords: duration, smartphone, sleep quality